2016
DOI: 10.12669/pjms.323.9399
|View full text |Cite
|
Sign up to set email alerts
|

Effect of angiotensin converting enzyme inhibitoron glomerular hyperfiltration in patients with type 1 diabetes

Abstract: Objective:To assess the effect of angiotensin converting enzyme inhibition on glomerular filtration rate (GFR) in normotensive patient with type 1 diabetes.Methods:A two year non-placebo control prospective study was conducted after ethical approval at Diabetes Centre of Diabetic Association of Pakistan, a WHO collaborating centre in Karachi, Pakistan. All patients with type 1 diabetes visited the out-patients department from August 2009 till July 2011 and those who fulfilled the inclusion criteria were invite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…An effect of this interaction might be expected because hyperfiltration, which is reported in formerly preeclamptic women, 10 influences the effect of ACE inhibitor/ARB on eGFR. 20 All analyses were performed using an exchangeable correlation matrix structure, assuming a fixed correlation between measurements. In all analyses, P < 0.05 indicated statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…An effect of this interaction might be expected because hyperfiltration, which is reported in formerly preeclamptic women, 10 influences the effect of ACE inhibitor/ARB on eGFR. 20 All analyses were performed using an exchangeable correlation matrix structure, assuming a fixed correlation between measurements. In all analyses, P < 0.05 indicated statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“… 11 GFR is the most reliable clinical indicator to measure renal functions as it emulates the functioning of nephrons. 12 An acute but reversible decline in eGFR referred as GFR ‘dip’ has been linked to the usage of SGLT2 inhibitors in CHF. 13 Keeping this in consideration we evaluated eGFR in our study and demonstrated that a similar trend of transient rebuff was observed by both groups which was insignificant when compared between groups.…”
Section: Discussionmentioning
confidence: 99%
“… 11 Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) equation was employed to calculate eGFR by using serum creatinine levels. 12 Secondary outcomes included weight loss during hospitalization, dose of furosemide, and length of hospital stay.…”
Section: Methodsmentioning
confidence: 99%